2011
DOI: 10.1002/tea.20435
|View full text |Cite
|
Sign up to set email alerts
|

In Quest of productive modeling‐based learning discourse in elementary school science

Abstract: The purpose of this study was to investigate whole classroom discourse during modeling‐based learning in science, seeking to describe the discourse's characteristics, its relation to the micro‐context in which it took place and to the student‐constructed models, and to ascertain when it becomes productive. Additionally, we aimed to describe how whole classroom modeling discourse in science may be better supported by the teacher as well as the role of the modeling tool. In doing so, we analyzed student conversa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
62
0
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(70 citation statements)
references
References 61 publications
3
62
0
5
Order By: Relevance
“…This is because model generation is not about a simple description of a phenomenon; instead, it is similar to the process of creating a new concept using various representation skills (Wells et al 1995). In this phase, students collect data that can be used as evidence in order to produce the best model to describe the phenomenon (Louca et al 2011). The knowledge to be used as evidence may be obtained through experiments, from a literature review, or it might already exist as prior knowledge (Justi and Gilbert 2002).…”
Section: Model Generation Phasementioning
confidence: 99%
See 1 more Smart Citation
“…This is because model generation is not about a simple description of a phenomenon; instead, it is similar to the process of creating a new concept using various representation skills (Wells et al 1995). In this phase, students collect data that can be used as evidence in order to produce the best model to describe the phenomenon (Louca et al 2011). The knowledge to be used as evidence may be obtained through experiments, from a literature review, or it might already exist as prior knowledge (Justi and Gilbert 2002).…”
Section: Model Generation Phasementioning
confidence: 99%
“…In the same manner, Windschitl et al (2008) claimed that modelbased inquiry supported the five epistemic features of scientific knowledge: It is testable, revisable, explanatory, conjectural, and generative. Some previous studies explored secondary students' modeling practice with the help of the teacher (e.g., Louca et al 2011;Mendonça and Justi 2013;Núñez-Oveido et al 2008;Passmore and Svoboda 2012) and investigated the epistemic value of modeling by only focusing on the model evaluation phase (e.g., Lee and Kim 2014;Nelson and Davis 2012;Penner et al 1997). However, our study findings have the possibility of reinforcing the epistemic value of group modeling practice by exploring the students' argumentative interaction in all modeling phases such as model generation, elaboration, evaluation, and modification.…”
Section: Experience Caused By the Statements Associated With Dla In Gmentioning
confidence: 99%
“…The Consortium for Policy Research in Education report Learning Progressions in Science: An evidence-based approach to reform (Corcoran et al 2009) identified learning progressions as a promising model that can advance effective adaptive instruction teaching techniques and thereby change the norms of practice in schools. A number of learning progressions in science have incorporated components of QR (Louca et al 2011;Pluta et al 2011;Schwarz, et al, 2009;Stefani and Tsaparlis 2009;Taylor and Jones 2009;Lehrer andSchauble 2002, Smith et al 2006), but the one proposed here is the first progression specifically addressing the development of QR in the sciences.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Ao contrário dos modelos mentais, os modelos científicos resultam da criação específica dos dos estudantes (Louca et al 2011, Palmero 2008. No caso concreto do ensino das Geociências, a modelação 1 apresenta-se como uma ferramenta fulcral pois, a recriação dos fenómenos geológicos através de modelos pode reduzir milhões de anos a algumas horas ou minutos ), e permite recriar fenómenos que não são facilmente observáveis num contexto real, como é o caso dos riscos naturais.…”
Section: Introductionunclassified